Cryptococcal Anterior Glottic Web from Disseminated Infection Presenting as Confusion: A Case Report. (February 2021) - Haught, Erica; Roberts, Christopher; McChesney, Jason
Objectives: To educate healthcare providers on Cryptococcus neoformans as a novel cause of glottic webs especially in an immunocompromised patient and discuss recurrence of the glottic web. This case also emphasizes the importance of a comprehensive patient evaluation in cases such as this, as laryngeal involvement in this case was only a portion of the patient's disease burden. Methods: An extensive review of the patient's clinical course was assessed including patient presentation, diagnostic techniques, medical and surgical treatment, and complications. Results: Prolonged Fluconazole therapy and two excisions of the glottic web, the second with keel placement, was an effective treatment course for our patient. Conclusion: Cryptococcal glottic webs are rare, and this case report demonstrates successful treatment in one such case with operative intervention following medical management of disseminated disease.